Keywords: methods، investigation، reform، thought، doctrine، Islam - Hamid Hadi Baden ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The Noble Qur’an has spoken at length about reform in general، and the word “reform” is mentioned in the Noble Qur’an in more than one hundred and eighty places. This word، despite its various derivations، is abundant material in which the Book of God، peace and blessings be upon him، abounds. It carries within it multiple colors and various features and methods، in reference to the importance of reform. Reform and its role in overcoming problems and addressing ways of corruption at the individual level or at the societal level، whether in terms of economics، politics، thought، culture، or education. God، may God bless him and grant him peace، has perfected His religion and completed His blessings upon the believers through what He revealed of the Noble Qur’an to the Seal of the Prophets and Messengers، Muhammad (peace be upon him). May God’s prayers and peace be upon him and his family to bring people out of darkness into light، and guide them to the straight path of God. God Almighty said: ( There has come to you from Allâh a light and a plain Book (this Qur’ân). Wherewith Allâh guides all those who seek His Good Pleasure to ways of peace، and He brings them out of darkness by His Will unto light and guides them to the Straight Way (Islâmic Monotheism) ). ( ) Islam took over the leadership of humanity after the earth was corrupted and humanity tasted the calamities. There are a number of toxins that have crept into our thoughts and must be